Therapeutic Effects of Proprotein Convertase Subtilisin/Kexin Type 9 Inhibitors in Dyslipidemia: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Hikmayani, Nur Hafidha; Febrinasari, Ratih Puspita; Satwika, Ariq Ratya (Althea Medical Journal, 2025)
Background: Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors represent a novel class of medications for managing dyslipidemia. Although previous meta-analyses have confirmed their efficacy in lowering low-density lipoprotein cholesterol (LDL-C), few have evaluated their effects on broader lipid parameters. Moreover, most studies focus on the general dyslipidemic population, provided limited insight into specific subgroups. This study specifically investigated the effects of PCSK9 inhibitors on multiple lipid parameters in individuals with dyslipidemia who were statin-intolerant, statin-resistant, or required intensified lipid-lowering treatment.Methods: This study systematically searched PubMed, ScienceDirect, and the Cochrane Library for phase 3 randomized controlled trials (2013-2023), evaluating PCSK9 inhibitors against placebo or non-statin standard care in dyslipidemic patients aged ≥18 years. The main outcome was the changes from baseline in lipid parameters. Random-effects meta-analyses were conducted using RevMan. Results: Eight studies involving 2,343 participants met eligibility criteria. PCSK9 inhibitors significantly reduced LDL-C (MD -46.8, 95% CI [-53.2; -40.4]), non-HDL-C (MD -41.1 [-46.9; -35.3]), total cholesterol (MD -31.5 [-37.8; -25.2]), triglycerides (MD -11.7 [-15.0; -8.4], Lp(a) (MD -19.2 [-25.7; -12.6]), and ApoB (MD -39.4 [-45.0; -33.7]). PCSK9 inhibitors also significantly increased HDL-C (MD 6.3 [4.7; 7.9]) and ApoA-I (MD 4.1 [2.8; 5.5]).Conclusion: PCSK9 inhibitors significantly improve a broad spectrum of lipid parameters, including non-traditional markers such as non-HDL-C, ApoA-I, ApoB, and Lp(a), underscoring their potential role in managing dyslipidemia, particularly in patients inadequately controlled with standard therapies.